2018
DOI: 10.1111/1467-9566.12780
|View full text |Cite
|
Sign up to set email alerts
|

Social practice, plural lifestyles and health inequalities in the United Kingdom

Abstract: Persistent health inequalities pose a continued research and policy challenge in the United Kingdom and elsewhere. Current approaches to health research and promotion are predicated on a distinction between wider, social structural causes and individual, health-related behaviours often conceived of as lifestyle choices. Drawing on Bourdieu's theory of social practice, this paper develops an integrated perspective by observing associations between health and structured lifestyle practices. Using the UK Understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…This corresponds to contemporary theories of social practice that suggest that “interventions to improve the health of populations and create positive social change will be better served by targeting social practices rather than the attitudes, behaviour and choices of individuals” [ 66 ]. In these theories, health and wellbeing are considered outcomes of a set of social practices, part of everyday life, and not only the result of a healthy lifestyle [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to contemporary theories of social practice that suggest that “interventions to improve the health of populations and create positive social change will be better served by targeting social practices rather than the attitudes, behaviour and choices of individuals” [ 66 ]. In these theories, health and wellbeing are considered outcomes of a set of social practices, part of everyday life, and not only the result of a healthy lifestyle [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, strategies to reduce health inequities should be based on an ecological perspective, target the social determinants of health, and address factors at multiple levels and the interaction between factors [7][8][9]. Research on health inequities within different lifestyle groups has shown that individual health-related behaviors are bound up in activities that correspond to the person's context (habitus) combined with his/her position in social space and subjective perceptions [10]. Consequently, health promotion ought not to target the individual health-related behavior or social participation/engagement in the neighborhood but rather consider the underlying drivers and their causes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…their CHL), we call upon Pierre Bourdieu’s theory of practice ( Bourdieu, 1977a ; Bourdieu and Passeron, 1990 ) and his concepts of habitus and capital ( Abel and Frohlich, 2012 ). Bourdieu’s theory of practice has been successfully applied to study how health inequalities are reproduced ( Williams, 1995 ; Veenstra 2007 ; Schori et al 2014 ; Jeong and Veenstra, 2017 ), including social patterning of health lifestyles, beliefs and health behaviours ( Cockerham et al, 1997 ; De Clercq et al, 2017 ; Gagné et al, 2018 ; Kandt, 2018 ).…”
Section: Critical Health Literacy and The Reproduction Of Inequality—...mentioning
confidence: 99%
“…Further, Bourdieu's concepts of capital as a classificatory mechanism and as a driver of social hierarchy and division of both urban social and geographical space will be discussed in the context of urban health inequalities (cf. Kandt, 2015Kandt, , 2018. In particular, it will be discussed in relation to urban disparities and the determinants of a heathy lifestyle in Sheffield's socially and geographically divided space (ibid.…”
Section: Objectified Cultural Capitalmentioning
confidence: 99%
“…Spatial deprivation in less affluent neighbourhoods creates significantly distinctive (unhealthy) lifestyles compared with more affluent neighbourhoods (Brownson, Fielding & Maylahn, 2009;Estabrooks, Lee & Gyurcsik, 2003;Kandt, 2015Kandt, , 2018. In the context of a healthy lifestyle, the stratified structure of urban areas and the geographical position and quality of neighbourhoods, seems particularly interesting.…”
Section: Spatial Distribution Of Capital Reflecting the Inequality An...mentioning
confidence: 99%